2014
DOI: 10.1371/journal.pone.0088160
|View full text |Cite
|
Sign up to set email alerts
|

Whitebark Pine, Population Density, and Home-Range Size of Grizzly Bears in the Greater Yellowstone Ecosystem

Abstract: Changes in life history traits of species can be an important indicator of potential factors influencing populations. For grizzly bears (Ursus arctos) in the Greater Yellowstone Ecosystem (GYE), recent decline of whitebark pine (WBP; Pinus albicaulis), an important fall food resource, has been paired with a slowing of population growth following two decades of robust population increase. These observations have raised questions whether resource decline or density-dependent processes may be associated with chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…Our study findings corroborate those of Bjornlie et al (), who reported evidence of an inverse relationship between home‐range size and the index of grizzly bear population density; they did not observe a relationship between home‐range size and availability of live whitebark pine stands. Combined, these studies provide evidence that grizzly bear density may become an increasingly important factor to consider for management of the grizzly bear population in the GYE.…”
Section: Management Implicationssupporting
confidence: 92%
See 3 more Smart Citations
“…Our study findings corroborate those of Bjornlie et al (), who reported evidence of an inverse relationship between home‐range size and the index of grizzly bear population density; they did not observe a relationship between home‐range size and availability of live whitebark pine stands. Combined, these studies provide evidence that grizzly bear density may become an increasingly important factor to consider for management of the grizzly bear population in the GYE.…”
Section: Management Implicationssupporting
confidence: 92%
“…These cells were not solvable in terms of correlations and were excluded. Of the remaining cells ( n = 250), we detected little correlation between the rate of change of the cumulative capture index and that of the density index: the distribution of correlation coefficients for these 250 cells approached a normal distribution with a mean near 0 (truex¯=0.07;σ=0.28; Bjornlie et al ). The second caveat is that the initial and ending years from 1975 to 2012 underestimated density relative to the middle years of this period.…”
Section: Methodsmentioning
confidence: 83%
See 2 more Smart Citations
“…Grizzly bears are a known predator of elk calves and may strongly influence calf recruitment (Barber‐Meyer et al , Griffin et al ); thus, we developed an index of grizzly bear density. We estimated the index using procedures developed by the Interagency Grizzly Bear Study Team (IGBST; see Bjornlie et al for in‐depth description). The index is derived from capture and telemetry locations of known‐age individuals ≥2 years old in conjunction with survival records to back‐ and forecast lifetime home ranges.…”
Section: Methodsmentioning
confidence: 99%